Percolation characteristics of filled polyurethane auxetics - Shevchuk, T.M.; Bordyuk, M.A.; Mashchenko, V.A.; Kvasnikov, V.P.; Krivtsov, V.V. (Physics and Chemistry of Solid State, 2022)
According to the experimental values of the propagation velocities of longitudinal and transverse ultrasonic waves, the Poisson's ratio of polyurethane systems filled with metal particles was determined. For such systems, the Poisson's ratio is negative. Its value for metal-filled polymer auxetics with polyurethane matrix allowed to determine fractal dimensions and critical percolation indices. This approach made it possible to clarify the features of structure formation in polymer auxetics. It is shown that the fractal-percolation characteristics of these systems are determined by the type of metal filler and the size of its particles.